Burkitbayev M.M., Kurmanbayeva M.S., Bachilova N.V., Erezhepova N.Sh., Jumakhanova G.B., Khodjabayeva D.A. Effciency of Sulfur-Containing Nanocomposites and Drugs on the Productivity of Wheat (TRITICUM L.): Al-Farabi Kazakh National University, Kazakhstan, Almaty (Eurasian Journal of Ecology, 2018)
)The problem of increasing the yield of wheat has always been a priority not only for the country,but for the world’s population as a whole, because, bread is an important part of nutrition. All the studies conducted on wheat are aimed at increasing the productivity. Our research also touched this topicalissue. To achieve reliable results, wheat must be grown for at least 3 years in the field, but in the greenhouse conditions, this period can be reduced by half. The greenhouse of Al-Farabi Kazakh National University was first launched in 2016. The use of fertilizer by drip irrigation is an effective and convenientmethod for growing cereal crops. Lately, many different expensive fertilizers, but not all are effective andincrease yields. Sulfur is an essential element like nitrogen, phosphorus and potassium. Sulfur is the active center of many enzymes, is part of proteins and is a participant in their synthesis. The lack of sulfurleads to the accumulation of non-protein nitrogen, resulting in a reduced response to nitrogen fertilizers.In connection with the in-depth study of the effect of sulfur-containing products on wheat productivity, research began in 2017 in greenhouse conditions (Greenhouse of al-Farabi KazNU) for testing newsulfur-containing nanocomposites and preparations obtained by synthesizing. Studies of the influenceof sulfur on the productivity of wheat grains abroad, the aim of our study is to synthesize products usingsulfur resources of Kazakhstan to easily and effectively meet the domestic needs of fertilizers. The studies were conducted in 4 versions, 1-control variant; 2-solution of sulfur nanocomposites; 3-pasty sulfur;4-dry state of sulfur. Since sulfur is important in seed productivity, it was found in the course of the studythat in variants with sulfur-containing preparations, the number of productive shoots, the number andweight of grains increased, compared to the control. The use of a new preparation as a fertilizer showedearly maturing of wheat for 3-4 weeks. Because, sulfur contributes to the rapid growth of wheat. In thenorthern regions of the country, where the winter comes early, the wheat does not have time to ripen.Wheat requires additional sulfur for rapid growth and development. The results of the study show thatnew sulfur-containing preparations are effective and beneficial for obtaining early and high yield, therefore we recommend using tested sulfur preparations in the field of agriculture.Key words: sulfur, solution of the nanosulfur drug, paste-like nanosulfur drug, dry nanosulfur drug,wheat, greenhouse, yield.